IoT and AI for Smart Grid Optimization in Urban Areas - Pal, Gourab (Soft Computing Fusion with Applications, 2025)
As cities grow and the need for energy rises, optimizing power distribution and enhancing grid efficiency becomes vital. This study explores how the integration of the Internet of Things (IoT) and Artificial Intelligence (AI) can be utilized to improve smart grid systems in urban areas. This strategy aims to enhance energy distribution, cut down on inefficiencies, and lessen power outages by using IoT devices for immediate data gathering and AI-powered predictive algorithms for informed decision-making. Additionally, the system's capability to identify irregularities and forecast equipment failures aids in lowering maintenance expenses. Simulation results from a model urban grid indicate that smart grid solutions driven by AI and IoT can result in superior energy management, greater grid reliability, and promote more sustainable development in urban settings.